Hyperactive glial cells contribute to axonal pathologies in the spinal cord of Npc1 mutant mice. Issue 7 (19th March 2014) - Yan, Xin; Yang, Fan; Lukas, Jan; Witt, Martin; Wree, Andreas; Rolfs, Arndt; Luo, Jiankai
<x xml:space="preserve">Abstract</x> Niemann‐Pick disease type C1 (NPC1) is a neurodegenerative disease with various progressive pathological features, for example, neuronal loss, dysmyelination, abnormal axon swelling, and gliosis, in the brain. Pathological activation of p38‐mitogen‐activated protein kinase (MAPK) results in hyperphosphorylation of tau protein, which contributes to the development of neurodegenerative diseases. In this study, axonal varicosities or spheroids and presynaptic aggregates in the spinal cord of the Npc1 mutant mice were found from postnatal day (P) 35 onwards, as indicated by the increased hyperphosphorylated neurofilament and synaptophysin immunoreactivity as well as the findings from electron microscopy. However, activities of astrocytes and microglia in the Npc1 mutant spinal cord were progressively increased earlier from P10 onwards, accompanied by increased expression of interleukin‐1β and apolipoprotein E, as well as up‐regulated p38‐MAPK activity and enhanced phosphorylated tau protein, but not cyclin‐dependent kinase 5/p35 complex and glycogen synthase kinase‐3β. Taken together, our data suggest that the axonal pathologies in the Npc1 mutant spinal cord are strongly correlated with the increase of activated glial cells, which produce IL‐1β and ApoE, resulting in the activation of p38‐MAPK signaling pathway and enhanced phosphorylated tau protein. GLIA 2014;62:1024–1040